Post SARS-CoV-2 infection and hair loss - Fahad H Alrashidi; Nojoud Alaroush (Wolters Kluwer Medknow Publications, 2022)
People affected with severe acute respiratory syndrome coronavirus 2 can have a wide variety of symptoms. Literature and public discussion forums report persistent symptoms among COVID-19 survivors. More than 25% of COVID-19 survivors report hair loss as a persisting issue. The Centers for Disease Control and Prevention state that hair loss as a potential long-term effect of COVID-19 is currently under investigation. This report may be the first case of hair loss in the patient with postCOVID-19 infection in Saudi Arabia.